2018
DOI: 10.1093/humupd/dmy007
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, obesity and the prevalence of impaired glucose tolerance and type 2 diabetes in PCOS: a systematic review and meta-regression

Abstract: CRD42017056524.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
180
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(199 citation statements)
references
References 70 publications
6
180
1
12
Order By: Relevance
“…These results suggested that the association between H. pylori and diabetes was not a consequence of higher eradication failure in individuals with diabetes. It is suspected that there is an association between polycystic ovary syndrome (PCOS) and type 2 diabetes mellitus. It is also reported that there might be an association between PCOS and H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the association between H. pylori and diabetes was not a consequence of higher eradication failure in individuals with diabetes. It is suspected that there is an association between polycystic ovary syndrome (PCOS) and type 2 diabetes mellitus. It is also reported that there might be an association between PCOS and H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is an endocrine disorder with a reported overall prevalence rate of 6% to 10% [1] based on the Rotterdam diagnostic criteria of two of three features, i.e., oligoor anovulation, hyperandrogenism (clinical or biochemical), and polycystic ovaries on ultrasound, after exclusion of other causes [2]. PCOS is associated with reproductive (hyperandrogenism, anovulation, infertility, and pregnancy complications) [3] and metabolic features (elevated prevalence of and risk factors for type 2 diabetes and cardiovascular disease) [4,5], along with psychological impact, such as increased risk of depression and anxiety [6] and impaired quality of life [7]. Insulin resistance is a key pathophysiological contributor to PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…По данным метаанализа 35 исследований, проведенного N.S. Kakoly et al (2018), у женщин с СПКЯ чаще отмечались НТГ, СД 2-го типа и метаболический синдром [11]. В датском популяционном исследовании 2017 г. частота развития СД 2-го типа была в 4 раза выше у женщин с СПКЯ по сравнению с группой контроля, кроме того, СД 2-го типа был диагностирован в более молодом возрасте у пациенток с установленным диагнозом СПКЯ [12].…”
Section: Discussionunclassified